The effect of Vigna unguiculata on the estrogen receptor-α expression and the endometrial thickness in rats treated with depot medroxyprogesterone acetate (DMPA) - Rizki Fitrianingtyas; Indah Christiana; Ririn Handayani; Ernawati Anggraeni; Zaida Mauludiyah; Sholihatil Hidayati (PAGEPress Publications, 2023)
Depot medroxyprogesterone acetate (DMPA) is a contraceptive method that prevents ovulation and reduces endometrial thickness. This study aimed to investigate the influence of Vigna unguiculata (VU) on estrogen receptor-α expression and endometrial thickness in rats subjected to DMPA treatment. The research utilized a true experimental design involving 25 female Wistar rats divided into 5 experimental groups. The DMPA+VU experiment lasted for 4 weeks, and data were analyzed using a Complete Randomized Design. Estrogen receptor-α expression in the endometrium was assessed through immunohistochemical techniques, and endometrial thickness was determined via Hematoxylin-eosin (HE) staining, observed under dot slide microscopes (Olympus XC10) at 400× magnification. The study found that estrogen receptor-α expression and endometrial thickness were significantly higher in both the DMPA+VU2 and DMPA+VU3 groups compared to the DMPA group and the DMPA+VU1 group (p<0.05). DMPA treatment reduced estrogen receptor-α expression and endometrial thickness. However, the administration of Vigna unguiculata extracts at 2.5 mg/kg and 5 mg/kg led to an increase in estrogen receptor-α expression and endometrial thickness. The study implies that VU extract may have a positive impact on estrogen receptor-α expression and endometrial thickness in rats treated with depot medroxyprogesterone acetate.